Prognostic Factors for Refractory Chronic Rhinosinusitis in Patients Chronic Rhinosinusitis Concomitant Asthma : An Evidence Based Case Report - Kartika Dwiyani; Eka Dian Safitri; Yupitri Pitoyo (PERHATI-KL, 2018)
Background: In chronic rhinosinusitis (CRS) patients concomitant with asthma, more severe sinus disease has been reported and recurrence rate remains significant after optimal management. In this review, patients with CRS concomitant with asthma which had optimal management will be analyzed. Did several factors e.g. mucosal eosinophilia, high eosinophil count, high Lund MacKay score, severity of asthma, peripheral blood count and type of surgery, affect the recurrence of rhinosinusitis? Purpose: To investigate prognostic factors for the recurrence or refractory in CRS patients concomitant with asthma. Case Report: Female, 31 years old, suffered CRS with nasal polyp concomitant with asthma. She had recurrence of her sinus disease although she had already received optimal management. Methods: Using Medline, Cochrane database and Hand searching to search for the evidence. The evidence selected was appraised by at least two members of our group using Oxford Centre for Evidence-based Medicine (CEBM) worksheet. Result: Two valid prognostic articles were appraised for the validity, importance and applicability in our clinical scenario. Conclusion: In this evidence-based case report, the type of surgery could affect the olfactory function and endoscopic postoperative score in CRS patients concomitant with asthma. It was found that Extensive Endoscopic Sinus Surgery (EESS) contributed as a prognostic factor to improve olfactory Visual Analog Scale (VAS) score and endoscopic postoperative score. Latar belakang: Pada pasien rinosinusitis kronis (RSK) yang disertai dengan asma telah banyak dilaporkan gejala sinus yang lebih berat dan angka kekambuhan yang signifikan walaupun pasien telah mendapatkan tatalaksana optimal. Dalam laporan ini, akan dianalisis pasien RSK yang disertai asma, yang telah mendapat terapi optimal. Apakah faktor-faktor eosinofilia pada mukosa, tingginya hitung jumlah eosinofil, tingginya skor Lund-MacKay, derajat keparahan asma, hitung jenis darah perifer dan jenis operasi, berperan terhadap kekambuhan rinosinusitis? Tujuan: Mengetahui faktor prognostik yang mempengaruhi kekambuhan pada pasien RSK yang disertai asma. Laporan kasus: Pasien wanita 31 tahun, dengan diagnosis RSK dengan polip yang disertai asma. Pasien mengalami kekambuhan rinosinusitis walaupun telah mendapatkan terapi optimal. Metode: Pencarian bukti dilakukan melalui Medline, Cochrane, Hand searching. Artikel yang didapat ditelaah oleh setidaknya dua anggota kelompok dengan menggunakan lembar kerja yang diperoleh dari Oxford Centre for Evidence-based Medicine (CEBM). Hasil: Dua artikel prognosis yang didapat, ditelaah kritis untuk dinilai validitas, pentingnya, dan kemampuan untuk dapat diaplikasikan dalam skenario klinis. Kesimpulan: Pada laporan kasus berbasis bukti ini, jenis operasi dapat merupakan faktor prognostik dalam memperbaiki skor Visual Analog Scale (VAS) olfaktori dan skor endoskopi pasca operasi. Extensive endoscopic sinus surgery (EESS) memiliki kontribusi sebagai faktor prognostik dalam memperbaiki skor VAS olfaktori dan skor endoskopi pasca operasi.